Urgent vs. planned peritoneal dialysis initiation: complications and outcomes in the first year of therapy - Pilatti,Murilo (2022)
Abstract Introduction: Urgent-start peritoneal dialysis (US-PD) has been proposed as a safe modality of renal replacement therapy (RRT) for end-stage renal disease (ESRD) patients with an indication for emergency dialysis initiation. We aimed to compare the characteristics, 30-day complications, and clinical outcomes of US-PD and planned peritoneal dialysis (Plan-PD) patients over the first year of therapy. Methods: This was a single-center retrospective study that included incident adult patients followed for up to one year. US-PD was considered when incident patients started therapy within 7 days after Tenckhoff catheter implantation. Plan-PD group consisted of patients who started therapy after the breaking period (15 days). Mechanical and infectious complications were compared 30 days from PD initiation. Hospitalization and technique failure during the first 12 months on PD were assessed by Kaplan-Meier curves and the determinants were calculated by Cox regression models. Results: All patients starting PD between October/2016 and November/2019 who fulfilled the inclusion criteria were analyzed. We evaluated 137 patients (70 in the US-PD x 67 Plan-PD). The main complications in the first 30 days were catheter tip migration (7.5% Plan-PD x 4.3% US-PD - p= 0.49) and leakage (4.5% Plan-PD x 5.7% US-PD - p=0.74). Most catheters were placed using the Seldinger technique. The main cause of dropout was death in US-PD patients (15.7%) and transfer to HD in Plan-PD patients (13.4%). The occurrence of complications in the first 30 days was the only risk factor for dropout (OR = 2.9; 95% CI 1.1-7.5, p = 0.03). Hospitalization rates and technique survival were similar in both groups. Conclusion: The lack of significant differences in patients’ outcomes between groups reinforces that PD is a safe and applicable dialysis method in patients who need immediate dialysis.